1978
DOI: 10.1002/crat.19780130522
|View full text |Cite
|
Sign up to set email alerts
|

Deformation‐mechanism maps of the intermetallic compound MgZn2

Abstract: Dedicated to Professor Hermann NEELS on the occasion of his 65th birthday Stress-temperature curves at constant strain-rate have been summarized for steady-state flow conditions of single crystals and polycrystals, and fields of dominating microscopic mechanisms were proposed.Fur stationare FlieObedingungen von Ein-und Vielkristallen werden Spannurigs-Temperatur-Kurven bei konstanter Verformungsgeschwindigkeit und Felder dominierender mikroskopischer Mechanismen angegeben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Indeed, Krämer and Schulze [21] have reported -based on geometrical considerations -that deformation of Laves phases can occur by perfect dislocation glide of dislocations with a Burgers vector of 1 3 〈112 � 0〉 on basal and prismatic planes. This slip mode has been experimentally confirmed by several groups at temperatures above a homologous temperature of 0.6 Tm for the respective Laves phases [22,23,32,40]. As evident from Figure 8b, glide of a perfect dislocation with a Burgers vector 1 3 〈112 � 0〉 on the basal plane creates no stacking fault since a full translation of the lattice is created.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, Krämer and Schulze [21] have reported -based on geometrical considerations -that deformation of Laves phases can occur by perfect dislocation glide of dislocations with a Burgers vector of 1 3 〈112 � 0〉 on basal and prismatic planes. This slip mode has been experimentally confirmed by several groups at temperatures above a homologous temperature of 0.6 Tm for the respective Laves phases [22,23,32,40]. As evident from Figure 8b, glide of a perfect dislocation with a Burgers vector 1 3 〈112 � 0〉 on the basal plane creates no stacking fault since a full translation of the lattice is created.…”
Section: Resultssupporting
confidence: 61%
“…Krämer et al [21] have suggested that the Peierls barrier is very high in TCP phases due to their close and complex packing ('interlocking'). This is well described for the Laves phases [21][22][23][24][25][26], the most common group of TCP-phases, which are themselves also composed of a layered structure, i.e. an alternating stacking sequence of single and triple layers.…”
Section: Introductionmentioning
confidence: 82%
“…For other strain rates cf. [137]. The influence of Zn composition is also indicated (after Paufler [137]).…”
Section: Compoundmentioning
confidence: 97%
“…Summarizing the mechanical response of the hexagonal Laves phase MgZn 2 , deformation mechanism maps have been proposed [137]. Fig.…”
Section: Compoundmentioning
confidence: 99%
“…With an etch-pit technique, dislocation velocity versus stress data were obtained on both basal and prism planes [27,28]. This group also published extensive data on stress-strain behavior, creep, dislocation densities, slip bands, twinning, diffusion, deformation-mechanism maps [30], and the effect of varying stoichiometry (from 66.0 to 67.5 at% Zn) on dislocation behavior and mechanical properties [29]. However, as with MgCu, crystals, plastic deformation in MgZn, crystals was limited to temperatures above about 0.65Tm.…”
Section: Mechanical Properties Of Single-phase Alloysmentioning
confidence: 99%